Emerging Opportunity and Destiny of mcr-1- and tet(X4)-Coharboring Plasmids in Escherichia coli - Xiaoyu Lu; Xia Xiao; Yuan Liu; Ruichao Li; Zhiqiang Wang (Microbiology Spectrum, 2021)
ABSTRACT The emergence of the plasmid-mediated colistin resistance gene mcr-1 and the plasmid-mediated tigecycline resistance gene tet(X4) represents a significant threat to public health. Although mcr-1 and tet(X4) have been reported to coexist in the same isolate, there are no reports on the emergence of plasmids coharboring mcr-1 and tet(X4). In this study, we aimed to investigate the opportunities for the emergence of mcr-1- and tet(X4)-coharboring plasmids and their destiny in Escherichia coli. Two plasmids carrying both mcr-1 and tet(X4) were constructed through conjugation assays and confirmed by S1 nuclease pulsed-field gel electrophoresis (S1-PFGE) and Nanopore long-read sequencing. Seven evolved plasmids carrying mcr-1 and tet(X4) from one of the two plasmids were acquired after continuous evolutionary processes. The fitness effects of mcr-1- and tet(X4)-coharboring plasmids were studied by stability experiments, competition experiments, and growth curve measurements. A plasmid carrying mcr-1 and tet(X4) and conferring no fitness cost to its host strain E. coli C600 emerged after evolution during serial passages of bacteria. We proved that it can be anticipated that mcr-1 and tet(X4) could appear in a single plasmid, and the possibility of occurrence in field strains should be monitored constantly. The originally formed cointegrate plasmids coharboring mcr-1 and tet(X4) could evolve into a plasmid with lower fitness costs. This will undoubtedly accelerate the transmission of mcr-1 and tet(X4) globally. The findings highlighted the great possibility of novel hybrid plasmids positive for mcr-1 and tet(X4), and the risk is worthy of increasing attention and public concern globally. IMPORTANCE Tigecycline and colistin are used as last-resort therapies to treat infections caused by multidrug-resistant (MDR) Gram-negative bacteria. However, the emergence of the plasmid-mediated tigecycline resistance gene tet(X4) and the plasmid-mediated colistin resistance gene mcr-1 represents a significant threat to human health. A plasmid coharboring mcr-1 and tet(X4) has not emerged so far, but the potential risk should not be ignored. Plasmids coharboring such vital resistance genes will greatly accelerate the progression of pan-drug resistance among pathogens globally. Therefore, evaluation of the emerging opportunity for the mcr-1- and tet(X4)-coharboring plasmids and their destiny in E. coli is of great significance. We provide important insight into the contributions of intI1, IS26, a truncated ISCR2 (ΔISCR2), and IS4321R during the generation of cointegrate plasmids carrying mcr-1 and tet(X4) and highlight the importance of antimicrobials in the evolution and diversity of mcr-1- and tet(X4)-coharboring plasmids. We show that monitoring of the occurrence of mcr-1-carrying MDR plasmids and tet(X4)-bearing MDR plasmids in the same strain should be strengthened to avoid the formation of mcr-1- and tet(X4)-coharboring plasmids.